Bradykinin : from vasodilation to neuroinflammation - Couture, R. (Rejean) (Molecular mediators in health and disease, 2025)
Bradykinin: From Vasodilation to Neuroinflammation, the latest release in the Molecular Mediators in Health and Disease series is a comprehensive guide to the multi-functional peptide bradykinin and its impact across the human body. The early chapters provide an overview of the biosynthesis and metabolism of bradykinin, understanding its receptors and signaling pathways, and the therapeutic value of agonists and antagonists for targeting these. This book explores the role of bradykinin in vascular, renal, and brain function, as well as its influence on various conditions and diseases, including inflammation, pain, cardiovascular disease, renal disease, obesity, ischemic stroke, and infectious diseases, including Covid-19. In addition to its foundational knowledge, the book includes extensive coverage of bradykinin biochemistry and molecular biology. It highlights the therapeutic potential of bradykinin, making it an ideal reference for researchers working in these fields. The book serves as an invaluable resource for understanding the complex roles of bradykinin and its applications in medical research and treatment.